2022
DOI: 10.3892/etm.2022.11388
|View full text |Cite
|
Sign up to set email alerts
|

Multidisciplinary collaboration for the successful treatment of a giant hepatic solitary fibrous tumor protruding into the thorax: A case report

Abstract: Solitary fibrous tumors (SFTs) are composed of spindle cells and collagen fibers, and these form rare mesenchymal tumors. SFTs are most frequently observed in intrathoracic sites; however, they may also occur in extrathoracic sites, such as the liver. Unlike the hepatic SFTs (HSFTs) reported in the literature, the SFT detailed in the present case report was a large tumor that originated from the liver, with a dumbbell-shaped growth through the diaphragm into the right thoracic cavity. This posed substantial ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 53 publications
0
3
0
Order By: Relevance
“…[23] Study demonstrated that the 5-year survival rate of patients who underwent curative resection ranging from 59% to 100%, and 10-year survival ranging from 40% to 89% have been observed when choosing complete curative resection. [2,[24][25][26] Therefore, curative resection could significantly improve the prognosis of giant abdominal-pelvic SFT and the prognosis of SFTs is often associated with resectability. Most of abdominal-pelvic SFT have a good prognosis without postoperative recurrence or metastasis, the recurrence of tumor was statistically related to capsule integrity for giant SFT.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…[23] Study demonstrated that the 5-year survival rate of patients who underwent curative resection ranging from 59% to 100%, and 10-year survival ranging from 40% to 89% have been observed when choosing complete curative resection. [2,[24][25][26] Therefore, curative resection could significantly improve the prognosis of giant abdominal-pelvic SFT and the prognosis of SFTs is often associated with resectability. Most of abdominal-pelvic SFT have a good prognosis without postoperative recurrence or metastasis, the recurrence of tumor was statistically related to capsule integrity for giant SFT.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, patients require long-term follow-up, considering the relatively good prognosis of SFT, adjuvant chemoradiation therapy after surgery is not recommended. [2] Chemoradiation therapy is utilized in cases of non-resectable tumors. [27] Increasing number of studies suggest that radiation therapy may reduce local recurrence, but no increase overall survival time.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation